(untitled) (The Review of Diabetic Studies, 2025)
The role of paramedics in healthcare has traditionally been centered on emergency response and pre-hospital care; however, in recent years, their scope has expanded significantly to encompass integrated and multidisciplinary models of care. This transformation is driven by the rising demand for healthcare services, the global burden of chronic diseases, and the need to reduce hospital overcrowding and enhance system efficiency. Paramedics are increasingly being deployed beyond emergency departments, working collaboratively with physicians, nurses, pharmacists, and other professionals in community, primary, and urgent care settings. Within these integrated care frameworks, paramedics contribute to preventive health, chronic disease management, mental health support, palliative care, and telehealth-enabled interventions. Evidence from countries such as the United Kingdom, Canada, and Australia highlights the effectiveness of community paramedicine programs in improving patient outcomes, reducing unnecessary hospital admissions, and enhancing continuity of care. Despite these advances, challenges persist, including professional recognition, regulatory limitations, and variability in training and scope of practice across regions. This review synthesizes the current evidence on the evolving role of paramedics within integrated and multidisciplinary care, identifying key benefits, barriers, and opportunities for system-level transformation. By examining international models and emerging practices, the article underscores the potential of paramedics as essential contributors to modern healthcare systems and calls for policies that support their expanded role in improving patient-centered outcomes.